Age-related differences in memory for "who, " "when, " and "where" are detectable in middle-aged adults. Issue 5 (3rd September 2022) - Van Etten, Emily; Sumida, Catherine; Graves, Lisa; Holden, Heather; Lopez, Francesca; Mustafa, Andrea; Gilbert, Paul E.
ABSTRACT: Our study examined age-related differences across the adult lifespan using a recently developed test assessing memory for "who, when, and where" in addition to associations among these elements. Young (ages 18–25), middle-aged (ages 40–55), and older adults (ages 60+) were asked to remember a sequence of pictures of different faces paired with different places and place the pairs in the correct sequence. Young adults remembered significantly mores face-place pairs in the correct sequence than middle-aged ( p < .05) and older adults ( p < .05), but there were no significant differences between middle-aged and older adults. Furthermore, young adults remembered significantly more face-place pairs irrespective of sequence than older adults ( p < .05). However, there were no other significant differences among the groups.Using a rapidly administered test that integrates aspects of everyday episodic memory, we found evidence for age-related differences in test performance beginning in middle age.